PEG-PLA Nanoformulation for Breast Cancer Therapy - Kannapiran, Sushma; Vitta, Samhita; Ranganathan, Balu; Rajagopal, Vidhya; Jolius, Gimbun; Ballamurugan, Anbalagan (Society for Biomaterials and Artificial Organs, India, 2022)
Worldwide, breast cancer is the second most common type of cancer among women next to lung cancer. Recurrence is seen in 30% of patients treated in their early stages of breast cancer due to therapeutic inefficiency. Breast cancer accounts for 25% of women cancer patients. The major drawback of drugs is their side effects due to systemic delivery and non-targeted drug uptake. Nano formulations based drug delivery systems have the potential to ameliorate the problems associated with non-targeted delivery of potent drugs to the cancer cells thereby overcoming the side effects which at many times deprive the breast cancer patients the much-needed quality of life. Polymer nano formulations present advantageous properties as drug delivery systems when compared to conventional therapy. PEG-PLA nano formulations are biocompatible and biodegradable. The optimal size of nano formulation is 10-200 nm. Polylactic acid (PLA) is a biodegradable polymer and in aqueous environments, it is metabolized into water and carbon dioxide. Polyethelene glycol (PEG) presents outstanding properties like flexibility, biocompatibility, tailorable properties and good hydrophilicity. The copolymerised PEG-PLA has a great potential to be used for drug delivery systems as a nanocarrier. In PEG-PLA composition, PLA is hydrophobic and PEG is hydrophilic. A wide spectrum of drug molecules like anastrozole (ANS), methotrexate (MTX), bortezomib (BTZ), thioridazine (Thio) and doxorubicin (Dox) is loaded very effectively thereby increasing their efficacy. The main aim of the polymeric nano formulation is rate controlled and tissue targeted release of specific drugs. PEG-PLA nanoparticles can be used for their biodegradability and amphiphilic characteristics. The drug release of PEG-PLA nano formulations will be discussed in particular for their modifiable characteristics, chemical-mechanical properties and their therapeutic efficacy against breast cancer.